Effect of the Size and Position of a Damping Ditch on the Reduction of the Blasting Vibration - Baofu Duan; Shizhan Shen; Guoshan Ta; Kebin Sun; Wei Hou; Li Gu (Advances in Civil Engineering)
The size and position of the damping ditch have a direct impact on the blasting vibration. In order to explore the effect of damping ditches of different sizes and positions, we investigated field blasting in the A3 area of the second phase of the Lufeng Nuclear Power Plant project. The simulation software ANSYS/LS-DYNA was used to simulate the vibration propagation of damping ditches with different depths, widths, and positions. Secondly, the vibration data of the corresponding measuring points were collected and the amplitude reduction was analyzed in different situations. An analysis of the numerical simulation results showed that an increase in the damping ditch width increased the vibration amplitude at the top of the building. The depth and position of the damping ditch were the main factors affecting the damping performance. A regression analysis was conducted using the Sadove equation for vibration velocity. It was found that the regression coefficient of the Sadove equation did not meet the required standards when a damping ditch was present. The vibration attenuation equations were fitted for the top and the base of the building. The results of this study provide reference data for the excavation and arrangement of damping ditches in practical applications.